Synthesis and properties of hypervalent electron-rich pentacoordinate nitrogen compounds. Issue 19 (6th May 2020) - Yan, Chenting; Takeshita, Masato; Nakatsuji, Jun-ya; Kurosaki, Akihiro; Sato, Kaoko; Shang, Rong; Nakamoto, Masaaki; Yamamoto, Yohsuke; Adachi, Yohei; Furukawa, Ko; Kishi, Ryohei; Nakano, Masayoshi
Abstract : Structural characterization of hypervalent electron-rich pentacoordinate nitrogen species has long been a synthetic challenge. Here we report the first nitrogen cationic radical (11-N-5 ) species featuring a weak hypervalent 3c-5e interaction. Abstract : Isolation and structural characterization of hypervalent electron-rich pentacoordinate nitrogen species have not been achieved despite continuous attempts for over a century. Herein we report the first synthesis and isolation of air stable hypervalent electron-rich pentacoordinate nitrogen cationic radical (11-N-5 ) species from oxidation of their corresponding neutral (12-N-5 ) species. In the cationic radical species, the nitrogen centers adopt a trigonal bipyramidal geometry featuring a 3-center-5-electron hypervalent attractive interaction. The combination of single crystal X-ray diffraction analysis and computational studies revealed weak N–O interactions between the central nitrogen cation and oxygen atoms. This successful design strategy and isolation of air-stable pentacoordinate hypervalent nitrogen species allow further investigations on reactivity and properties resulting from these unusually weakly coordinating interactions in nitrogen compounds.